Automatic Image Enhancement by Noise Avoidance using Fuzzy and Histogram techniques - Murali, V; Venkateswarlu, T (International Journal of Computer Sciences and Engineering, 2019)
Automatic Image enhancement is one of the major concerns in the digital image processing. There are various methods to enhancement the image. Noise removal is one of the best followed approaches that results in better image. We are using fuzzy and histogram techniques to achieve it. In fuzzy based automatic image enhancement by noise avoidance using histogram technique, we have studied various fuzzy enhancement methods as wavelets that has different issues, and studied histogram hyperbolization. Fuzzy based noise avoidance technique makes use of noise cheating and correction and removal of grain noise. The results clearly show that, the proposed technique overcomes the existing limitations and removes the noise using encoder and decoder fuzzy mechanism thereby increasing automatically the image view using histograms.